2021
DOI: 10.1055/a-1496-8969
|View full text |Cite|
|
Sign up to set email alerts
|

Diagnosis and management of acute lower gastrointestinal bleeding: European Society of Gastrointestinal Endoscopy (ESGE) Guideline

Abstract: Main Recommendations 1 ESGE recommends that the initial assessment of patients presenting with acute lower gastrointestinal bleeding should include: a history of co-morbidities and medications that promote bleeding; hemodynamic parameters; physical examination (including digital rectal examination); and laboratory markers. A risk score can be used to aid, but should not replace, clinician judgment.Strong recommendation, low quality evidence. 2 ESGE recommends that, in patients presenting wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
147
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 135 publications
(161 citation statements)
references
References 163 publications
(261 reference statements)
4
147
0
10
Order By: Relevance
“…Although CT is more commonly performed in high-volume hospitals, the use of colonoscopy is the reverse of CT. Upper gastrointestinal bleeding should be suspected in cases of gastrointestinal bleeding with unstable vitals, even for patients presenting with acute hematochezia. CT was recommended as a first-line diagnostic modality www.nature.com/scientificreports/ for these patients [10][11][12][13][14] . Our finding that CT was performed more frequently in high-volume hospitals might explain the high proportion of patients with unstable vital signs, such as patients with upper gastrointestinal bleeding who presented with acute hematochezia.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although CT is more commonly performed in high-volume hospitals, the use of colonoscopy is the reverse of CT. Upper gastrointestinal bleeding should be suspected in cases of gastrointestinal bleeding with unstable vitals, even for patients presenting with acute hematochezia. CT was recommended as a first-line diagnostic modality www.nature.com/scientificreports/ for these patients [10][11][12][13][14] . Our finding that CT was performed more frequently in high-volume hospitals might explain the high proportion of patients with unstable vital signs, such as patients with upper gastrointestinal bleeding who presented with acute hematochezia.…”
Section: Discussionmentioning
confidence: 99%
“…A few recent studies have reported the therapeutic utility of ligation therapy for colonic diverticular bleeding 18,19 . Moreover, the guidelines for endoscopic clipping recommend that clips be placed onto the vessels by grasping directly, not in a zipper fashion, to ensure hemostatic effects [10][11][12][13][14] . However, the reason for the significant difference in the treatment methods between the groups was not clear in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations